Comparison of Febrile Infants With Enterococcal and Gram-negative Urinary Tract Infections. Issue 9 (September 2016) - Lubell, Tamar R.; Schnadower, David; Freedman, Stephen B.; Macias, Charles G.; Agrawal, Dewesh; Kuppermann, Nathan; Dayan, Peter S.
Abstract : Background: Few data exist on the presentations and clinical courses of infants with enterococcal urinary tract infections (UTI). The objective of this study was to compare the clinical presentation, sensitivity of urinalysis (UA) and Gram's stain, radiological abnormalities and adverse events of febrile infants with enterococcal UTIs to those with Gram-negative UTIs. Methods: Retrospective study of febrile (≥38.0°C) infants 29–60 days of age with UTIs at 20 emergency departments. UTI was defined as growth of (1) ≥50, 000 colony forming units (CFUs)/mL of a single pathogen; or (2) either 10, 000 to <50, 000 CFUs/mL or 10, 000–100, 000 CFUs/mL (depending on laboratory reporting) with a positive UA or Gram's stain. Results: Thirty-seven (2.0%) of 1870 infants with febrile UTIs had enterococcal UTIs. On bivariable analysis, infants with enterococcal UTIs more frequently had histories of prematurity, previous hospitalizations, histories of genitourinary abnormalities, previous UTIs and ill-appearance in the emergency department compared with infants with Gram-negative UTIs (all P <0.05). On multivariable analysis, ≥ grade 3 vesicoureteral reflux (adjusted odds ratio 3.2, 95% confidence interval: 1.4, 7.6) and hydronephrosis (adjusted odds ratio 3.3, 95% confidence interval: 1.4, 7.9) were associated with enterococcal UTIs. Both groups had similar low risks of adverse events or severe clinical courses. The urine white blood cell count alone or in combination with leukocyte esterase was more sensitive for Gram-negative than enterococcal UTIs (range 80.4%–93.9% vs. 50.0%–75.9%). Conclusions: Febrile infants with enterococcal UTIs had a low likelihood of adverse events or severe clinical course, similar to those with Gram-negative UTIs. Infants with enterococcal UTIs frequently had underlying hydronephrosis and/or vesicoureteral reflux. The preliminary diagnosis of enterococcal UTIs may be inaccurate if based on UA.